An unconventional impression method using implant mount: an alternative to open- and closed-tray impression technique - Nidawani, Prakash; Shiva Sai, Vemula; Nagoji, Pooja; Saumya, Singh; Girish, Galagali (International Journal of Dental Materials, 2023)
Background: Various impression techniques have been proposed for making implant prostheses. Impressions are made at implant level – closed and open tray impressions, as well as abutment level impressions. Closed and open tray copings are used to make the impressions. The limitations associated with the implant impression copings, including expensive ones, pose a significant challenge in limited mouth-opening cases, and customization of copings is not feasible.Aim: This study aimed to compare the dimensional accuracy of four impression methods, open-tray, closed-tray, disposable mount as coping and splinted mount as coping.Materials and methods: An ideal maxillary edentulous acrylic model was used with windows created at the canine and molar regions. Four analogues were implanted in the canine and molar areas to represent implants. The analogues were parallel to one other and were orientated at 0 degrees using the surveyor's assistance. Four groups were made: closed-tray, open-tray, implant mount as coping and splinted mount as coping. The custom trays were fabricated, accordingly. The implant-level impressions were made in all the groups using polyether impression material. The impressions were fitted with their respective impression copings with the analogues. The impressions were poured using die stone type-IV, and the casts were made. The resulting casts were 3D scanned, and a virtual model (.stl File) was created. Each .stl file was subjected to Geomagic software to evaluate the three-dimensional accuracy of conventional implant copings and implant mount as copings.Results: The Open-tray and the closed-tray groups exhibited the mean dimensional accuracy of 0.011±0.0016 µm and 0.018±0.0012 µm, respectively. The mount as coping and splinted mount displayed a mean dimensional accuracy of 0.017±0.0008 µm and 0.013±0.0020µm, respectively.Conclusions: This pilot study concludes that the implant mount can be used as implant impression coping and an alternative to the conventional impression coping.